18F FDG PET Cardiac Imaging for Myocardial Viability Assessment in NINMAS - Mandal, Tapati; Sultana, Sadia; Begum, Shamim MF; Banerjee, Sajal K; Ahmed, Chowdhury Meshkat (Bangladesh Journal of Nuclear Medicine, 2024)
Abstract not available Bangladesh J. Nuclear Med. 27(1): 95-99, 2024